A TOPSIS-Based Multicriteria Approach for Reservoir Assessment - Aires, Renan Felinto de Farias; Salgado, Camila Cristina Rodrigues (Sociedade & Natureza, 2024)
Abstract Water management in the Brazilian semi-arid region has been, for decades, a challenge for institutions and decision-makers due to its intrinsic characteristics. The density of human occupation makes the region very vulnerable to drought events and problems related to the quality and need for water use are central issues. For this reason, this study presents an approach to assess the situation of water reservoirs in the semiarid based on the Water Quality Index (WQI) and Multi-Criteria Decision Making (MCDM). The WQI was used to calculate water quality and later applied as a criterion for the MCDM model proposed. The model also considers the need and availability criteria to assess the reservoirs of the two largest drainage basins in Rio Grande do Norte state, Brazil. The MCDM method used was R-TOPSIS since it is more flexible and robust for future analyses in other situations. The results showed the condition of the reservoirs, in order to support decision-makers in the operation of these facilities and enable multiple use of the waters. The combined approach proposed may provide important contributions in the analysis of water reservoirs in order to supply the semiarid region, where water issue is critical.